Efficacy and Tolerability of the Association of Sibutramine and Orlistat for Six Months in Overweight and Obese Patients - Alfredo Halpern; Renata B. Pepe; Ana Paola Monegaglia; Mônica Beyruti; Maria Edna de Melo; Marcio C. Mancini (Journal of Obesity)
Objective. To assess the efficacy and tolerability of the association sibutramine (10–20 mg/day) and orlistat (120 mg 2-3 times a day) in the treatment of obesity in a six-month open trial. Methods. 446 overweight and obese patients who sought treatment for obesity in a private clinic were assessed every 2 weeks during a period of 3 and 6 months. Results. After 3 months, the mean weight loss was 10.5 kg (−9.8% of the initial weight, 𝑛=263), and after 6 months, the mean weight loss was 13.9 kg (−12.8% of the initial weight, 𝑛=97). The tolerability of such association was quite acceptable and coherent with the action mechanism of each component. Conclusions. The association of orlistat and sibutramine is quite efficient and it seems to promote a higher rate of weight loss than that reported in clinical studies performed with each drug separately.